2015
DOI: 10.1037/a0038547
|View full text |Cite
|
Sign up to set email alerts
|

Exploring links between early childhood educators’ psychological characteristics and classroom management self-efficacy beliefs.

Abstract: This study explored the predictive relations among early childhood educators' years of teaching experience, personality traits, and classroom management self-efficacy belief. Participants were n ϭ 395 early childhood educators (ECEs) from preschools and childcare centres located primarily in Ontario, Canada. Results showed positive relations between years of teaching experience and classroom management self-efficacy. As well, ECEs' personality predicted their classroom management self-efficacy above and beyond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
3
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 60 publications
(204 reference statements)
2
26
3
2
Order By: Relevance
“…Table 2 depicts descriptive statistics and inter-correlations for the teacher variables included in the study. Overall teacher self-efficacy is one of the highest reported in any empirical study solitarily focused on preschool teachers (Bullock et al, 2015;Guo et al, 2011aGuo et al, , 2010Kim & Kim, 2010;Woolfolk Hoy & Spero, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…Table 2 depicts descriptive statistics and inter-correlations for the teacher variables included in the study. Overall teacher self-efficacy is one of the highest reported in any empirical study solitarily focused on preschool teachers (Bullock et al, 2015;Guo et al, 2011aGuo et al, , 2010Kim & Kim, 2010;Woolfolk Hoy & Spero, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…The negative relationship between preschool teachers' professional experience and self-efficacy indicates that the occupation in the profession also causes exhaustion in teaching and negatively affects teacher self-efficacy (Bullock, Coplan and Bosacki, 2015;Toran and Gencgel, 2016). It was determined that the duration of professional experience of preschool teachers causes emotional exhaustion in the teachers and they become increasingly insensitive to the teaching process.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of PLC with nonprofessional caregivers, we also explore alternative possible moderators of pedagogical quality at the level of the individual caregiver, including psychological and demographic characteristics. The five personality traits have proved to be indicative of how professionals perform in various professions (Hogan & Holland, 2003), including professions involving interpersonal interactions (Mount, Barrick, & Stewart, 1998), work in ECEC (Bullock, Caplan, & Bosacki, 2015;Smidt, Kammermeyer, & Roux, 2015), and also in the context of homeschooling (Guterman & Neuman, 2018). Meta-analytical research has also demonstrated modest yet significant links between the personality traits of the Big Five framework and parenting in the case of both fathers and mothers (Prinzie, Stams, Dekovic, Reijntjes, & Belsky, 2009).…”
Section: Predictors Of Pedagogical Qualitymentioning
confidence: 99%